Kepatuhan self-efficacy pasien dalam mengontrol kadar glukosa darah pada pasien DMT2: Literatur review - Juraidah, Juraidah; Arofiati, Fitri (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a chronic disease whose prevalence continues to increase annually. Good blood glucose control is crucial in preventing complications and even death. The prevalence of diabetes mellitus cases in Indonesia in 2022 is very high, as evidenced by data showing reported cases of diabetes mellitus, with 463 million adults worldwide suffering from the disease. Purpose: To determine self-efficacy compliance for managing blood sugar in patients with type 2 DM. Method: This literature review study was conducted by searching various articles from various relevant sources. The literature was then categorized, analyzed, and summarized through journal screening. Results: Research articles were selected using various research methods related to self-efficacy and adherence in patients with type 2 diabetes. Ten articles were obtained: five using quantitative methods, one using qualitative methods, and three using descriptive methods. The details of the articles are summarized in one table. Conclusion: After analyzing several journals, the results showed that overall, self-efficacy has a very significant relationship with adherence in patients with type 2 diabetes. Keywords: Adherence; Self-efficacy. Pendahuluan: Diabetes melitus tipe 2 (DMT2) adalah penyakit kronis yang populasinya terus meningkat untuk setiap tahunya. Pengendalian glukosa darah yang baik sangat penting dalam mencegah komplikasi hingga kematian. Prevalensi kasus diabetes mellitus di tahun 2022 di Indonesia sangat tinggi dilihat dari data yang menunjukan laporan kasus diabetes mellitus dengan jumlah 463 juta orang dewasa di seluruh dunia yang menderita diabetes mellitus. Tujuan: Untuk mengetahui kepatuhan self efficacy untuk mengatur gula darah pada pasien DM tipe 2. Metode: Penelitian studi literatur review yang dilakukan dengan cara menelusuri berbagai artikel dari berbagai sumber yang relevan kemudian literatur dikelompokkan, dianalisis, diringkas melalui tahap screening jurnal. Hasil: Artikel penelitian dipilih menggunakan berbagai metode penelitian yang berkaitan dengan kepatuhan keyakinan diri pasien dengan diabetes tipe 2 didapatkan 10 artikel 5 artikel dengan metode kuantitatif dan 1 metode kualitatif, 3 artikel dengan metode deskriptif dan rincian artikel dirangkum dalam 1 table Simpulan: Setelah melakukan analisis dari beberapa jurnal didapatkan hasil bahwa adanya secara keseluruhan bahwa self efficacy mempunyai keterkaitan yang sangat signifikan dengan kepatuhan self efficacy pada pasien DM tipe 2. Kata Kunci : Kepatuhan; Self efficacy.